Implementation of Islamic Counseling Services as an Effort to Reduce Work-Related Stress among Police Officers in the North Sumatra Regional Police - Fajariah, Indah Suci; Madya, Efi Brata (UNIVERSITAS PAKUAN, 2023)
This study aims to explore the Implementation of Islamic Counseling Services as an Effort to Reduce Work-Related Stress among Police Officers in the North Sumatra Regional Police. The research employed a qualitative descriptive method, involving one counselor and four police officers as informants. The research took place at the Human Resources Bureau of the North Sumatra Regional Police from June 20 to June 30, 2023, utilizing data collection techniques such as observation, interviews, and documentation. Data were analyzed using a four-step analysis process: data collection, data reduction, data display, and data verification. Data validity was ensured through source, method, and time triangulation. The findings revealed that the application of Islamic counseling services in reducing work-related stress among police officers involved regular spiritual guidance sessions and counseling, addressing factors like location mismatch, family issues, economic concerns, heavy task pressures, and imbalanced income and expenses.